STANDAR MUTU PENDIDIKAN ISLAM DALAM PERSPEKTIFAKREDITASI DAN TATA KELOLA KELEMBAGAAN - Ulfiyah Ulfiyah; Qorina Widadiyah; Aisyah Fadiatu Rizqi (Universitas Islam Bunga Bangsa Cirebon, 2022)
Quality assurance in Islamic education institutions remains a pressing concern amid increasing national and global demands for educational accountability. Accreditation and institutional governance are two interdependent pillars that collectively determine the quality standards of Islamic educational institutions, yet their conceptual and operational integration has received insufficient scholarly attention. This study aims to examine quality standards in Islamic education through the lenses of accreditation frameworks and institutional governance practices, identifying the structural and cultural factors that influence their effectiveness. A systematic library research methodology was applied, drawing on reputable academic journals, policy documents, and scholarly books published between 2019 and 2024. Findings indicate that quality standards in Islamic education are shaped by a triadic relationship among regulatory compliance, leadership capacity, and community participation. Research gaps revealed that prior studies have largely examined accreditation and governance as separate domains without exploring their synergistic potential within Islamic educational contexts. This study proposes an integrative governance-quality model relevant to madrasah, Islamic universities, and pesantren environments.